2015
DOI: 10.1021/acssuschemeng.5b00519
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Nanoarchitecture of BiFeO3 Anchored TiO2 Nanotube Arrays for Electrochemical Energy Storage and Solar Energy Conversion

Abstract: Here, we report the synthesis of TiO 2 /BiFeO 3 nano-heterostructure (NH) arrays by anchoring BiFeO 3 (BFO) nanoparticles on TiO 2 nanotube surface and investigate their pseudocapacitive and photo-electrochemical properties considering their applications in green energy fields. The unique TiO 2 /BFO NHs have been demonstrated both as energy conversion and storage material. Capacitive behavior of the NHs has found to be significantly higher than the pristine TiO 2 NTs which is mainly due to the anchoring of red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(74 citation statements)
references
References 53 publications
(149 reference statements)
0
69
0
Order By: Relevance
“…It is also observed that as the scan rate is varied there is shift in the redox peaks, indicating the charge polarization. At lower scan rates, current response in the CV curve is reduced due to the increase in thickness of the diffusion layer, whereas the reverse trend is observed at higher scan rates due to the decrease in the thickness of the diffusion layer …”
Section: Resultsmentioning
confidence: 94%
“…It is also observed that as the scan rate is varied there is shift in the redox peaks, indicating the charge polarization. At lower scan rates, current response in the CV curve is reduced due to the increase in thickness of the diffusion layer, whereas the reverse trend is observed at higher scan rates due to the decrease in the thickness of the diffusion layer …”
Section: Resultsmentioning
confidence: 94%
“…The peak profiles and the characteristic binding energy values of Bi and Fe of bare and rGOÀAg-BFO nanostructures reveal the stable oxidization state of the elements, [28] which is + 3. The unaltered peak profiles, except a slight shift, signify that the integrated carrier materials i. e. Ag and rGO did not have lattice level or covalent interaction with the host BFO materials.…”
Section: Chemical State Analysismentioning
confidence: 99%
“…25 Sarkar et al showed that the TiO 2 /BiFeO 3 nanostructure yielded an enhanced capacitance of 440 F g À1 at a current density of 1.1 A g À1 in a 0.5 M Na 2 SO 4 aqueous solution. 26 The composite electrode can combine the large surface area of TNTs and the reversible electrochemical redox reaction of the electroactive materials, providing a better candidate for supercapacitors. 25 Bismuth molybdate (Bi 2 MoO 6 ), a typical layered Aurivillius oxide consisting of [Bi 2 O 2 ] 2+ layers sandwiched between [MO 4 ] 2À slabs, is widely used in photocatalytic applications due to its special physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%